Improving mental health and physiological stress responses in mothers following traumatic childbirth and in their infants: study protocol for the Swiss TrAumatic biRth Trial (START). Issue 12 (30th December 2019) - Sandoz, Vania; Deforges, Camille; Stuijfzand, Suzannah; Epiney, Manuella; Vial, Yvan; Sekarski, Nicole; Messerli-Bürgy, Nadine; Ehlert, Ulrike; Bickle-Graz, Myriam; Morisod Harari, Mathilde; Porcheret, Kate; Schechter, Daniel S; et al.
Abstract : Introduction: Emergency caesarean section (ECS) qualifies as a psychological trauma, which may result in postnatal post-traumatic stress disorder (PTSD). Maternal PTSD may not only have a significant negative impact on mother–infant interactions, but also on long-term infant development. The partner's mental health may also affect infant development. Evidence-based early interventions to prevent the development of postpartum PTSD in mothers are lacking. Immediately after a traumatic event, memory formation is vulnerable to interference. There is accumulating evidence that a brief behavioural intervention including a visuospatial task may result in a reduction in intrusive memories of the trauma. Methods and analysis: This study protocol describes a double-blind multicentre randomised controlled phase III trial testing an early brief maternal intervention including the computer game 'Tetris' on intrusive memories of the ECS trauma (≤1 week) and PTSD symptoms (6 weeks, primary outcome) of 144 women following an ECS. The intervention group will carry out a brief behavioural procedure including playing Tetris. The attention-placebo control group will complete a brief written activity log. Both simple cognitive tasks will be completed within the first 6 hours following traumatic childbirth. The intervention is delivered by midwives/nurses in the maternity unit. The primary outcome will be differences in the presence and severity of maternal PTSD symptoms between the intervention and the attention-placebo control group at 6 weeks post partum. Secondary outcomes will be physiological stress and psychological vulnerability, mother–infant interaction and infant developmental outcomes. Other outcomes will be psychological vulnerability and physiological regulation of the partner and their bonding with the infant, as well as the number of intrusive memories of the event. Ethics and dissemination: Ethical approval was granted by the Human Research Ethics Committee of the Canton de Vaud (study number 2017–02142). Dissemination of results will occur via national and international conferences, in peer-reviewed journals, public conferences and social media. Trial registration number: NCT 03576586.